Alice-Miranda at sea - Harvey, Jacqueline. (Delacorte Press, 2014)
"Alice-Miranda is set for a luxurious cruise aboard the royal yacht Octavia, where Aunty Gee is hosting the wedding of Aunt Charlotte and Lawrence Ridley. Wild weather and rumors of a jewel thief throw the travelers into turmoil, but something else is giving Alice-Miranda one of her strange feelings. Why does the ship's doctor look so familiar? And who is the shy blond boy hiding in one of the cabins? When Alice-Miranda seeks help from an unexpected source, will she and her helper manage to set things right in time for the celebrations?"--